Design of OCSRR-Based Differential Microwave Sensor for Microfluidic Applications - Yu, Jianyuan; Liu, Guohua; Cheng, Zhiqun; Song, Yu; You, Minghui (IEEE sensors journal, 2022)
In this article, a high-sensitivity differential microwave sensor based on open comprehensive split-ring resonator (OCSRR) is proposed to extract the complex dielectric constant of liquid samples. An OCSRR structure is etched on the metal plate attached to the upper layer of the substrate. In addition, the outer ring of OCSRR adopts a hexagonal structure to reduce the original capacitance of OCSRR, and the inner ring of OCSRR adopts a rectangular structure to facilitate optimization and obtain the highest electric field intensity. The polydimethylsiloxane (PDMS) microfluidic channel is placed on the side of the outer ring with high electric field intensity and injects different concentrations of water-ethanol mixture. During resonance, the electric field is concentrated along the slit where the microfluidic channel is located. When the liquid sample is injected, the corresponding reflection coefficient changes. The designed sensor is fabricated and tested, and the experimental results are in good agreement with the simulation results. Compared with the previous similar sensors, the sensor can suppress the influence of environmental factors and has an average high sensitivity of 0.88%.